The Validity of Mobile Learning-Based Ryleac Learning Tools for Strengthening Student Character - Tirtawaty Abdjul; Septiana Kurniasari; Samad Kadir (Universitas Muhammadiyah Sidoarjo, 2021)
Mobile learning-based learning is very appropriate to use in learning today, because students can be actively involved in learning and interact through mobile learning media to improve student character, the learning model that needs to be applied includes the Ryleac learning model. This study aims to produce a mobile learning-based Ryleac learning device for strengthening student character that is suitable for use in learning for class XI students of SMA Gorontalo. This research is classified as a Quasi Experiment research with a posttest only control group design. Based on the validity test, from the validation results by experts, it was found that the average ryleac-based mobile learning learning device for RPP obtained a validity value of 0.858 (SV), LKPD obtained a validity value of 0.870 (SV), teaching materials obtained a validity value of 0.859 (SV), THB obtained a validity value of 0.841 (V) and the student character observation sheet obtained a validity value of 0.889 (SV). Based on these data, the ryleac learning device based on mobile learning is feasible to use in learning.